2021
DOI: 10.1073/pnas.2018994118
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up real networks by geometric branching growth

Abstract: Real networks often grow through the sequential addition of new nodes that connect to older ones in the graph. However, many real systems evolve through the branching of fundamental units, whether those be scientific fields, countries, or species. Here, we provide empirical evidence for self-similar growth of network structure in the evolution of real systems—the journal-citation network and the world trade web—and present the geometric branching growth model, which predicts this evolution and explains the sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…In Ref. [30], it was also found that dynamical processes running on the replicas exhibit the same behaviour as in the original network, which enables not only to study dynamics on smaller substrates (with reduced computational costs), but also to analyze the dependence of dynamical processes on the system size even for real-world systems, for which one typically only has access to a single, fixed-size instance [31].…”
Section: B Geometric Renormalization Of Complex Networkmentioning
confidence: 98%
See 2 more Smart Citations
“…In Ref. [30], it was also found that dynamical processes running on the replicas exhibit the same behaviour as in the original network, which enables not only to study dynamics on smaller substrates (with reduced computational costs), but also to analyze the dependence of dynamical processes on the system size even for real-world systems, for which one typically only has access to a single, fixed-size instance [31].…”
Section: B Geometric Renormalization Of Complex Networkmentioning
confidence: 98%
“…While synthetic models allow for the generation of networks with an arbitrary number of nodes, with real networks one is limited to the observed ones. In order to obtain replicas of the network with different sizes, in this paper we employ a recently proposed technique based on the geometric renormalization group [30,31]. The method takes the original complex network and uses geometric scaling to renormalize it while preserving the overall structure of the network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many real systems evolve in a self-similar way that preserves their topology throughout the growth process over a long time span that is better explained by branching of fundamental units -whether those be scientific fields or countries (Zheng et al [2021]). The Geometric Branching Growth model predicts this evolution and explains the symmetries observed (Zheng et al [2021]). The model produces multiscale unfolding of a network in a sequence of scaled-up replicas preserving network features, including clustering and community structure.…”
Section: Geometry Of Weighted Multiplex and Growing Networkmentioning
confidence: 99%
“…In this framework, each node exists on a surface where a radial dimension encodes its popularity, or how likely it is to have many neighbors, and an angular dimension encodes the similarity between nodes, where similar nodes are more likely to be related [5]. The successes of hyperbolic network geometry cover a wide range of practical applications, like predicting economic patterns across time [6], making sense of the resilience of the Internet [1] or modeling information flow in the brain [2,7], to name a few. Furthermore, hyperbolic space is the only known metric space on which maximum-entropy random graphs can reproduce real network properties like clustering, sparsity, and heterogeneous degree distributions all at once [4].…”
Section: Introductionmentioning
confidence: 99%